The ProUni in the dissertations defended from 2007 to 2017: Where are the ProUni scholarship teachers in basic education? - Nalin, Jaime Antônio; Felicetti, Vera Lucia; Pauly, Evaldo Luis (Education Policy Analysis Archives, 2022)
The University for All Program (ProUni, abbreviation in Portuguese) provides the opportunity of access for determined groups of the population in the Brazilian Higher Education. Along these lines, based on dissertations defended in Brazil from 2007 to 2017, from the database of the Coordination for the Improvement of Higher Education Personnel (CAPES), this study aims to determine how the topic of ProUni has been studied and how the 1% (SISPROUNI, 2019) of grant-holding teachers are represented in these studies. Qualitative study that analyzed 42 dissertations. None of the studies analyzed included ProUni scholarship teachers. Many present the scholarship holders in general, while others present the professors of these scholarships, scholarship managers, and a few graduates of the program. Two categories emerged from the overall review of these dissertations: 1) ProUnistas and their social, cultural, economic, and academic contexts; and 2) state, government and private HEIs.